2012
DOI: 10.1111/j.1479-828x.2011.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of uterine artery embolisation for treatment of symptomatic fibroids and adenomyosis – An interim report on an Australian experience

Abstract: This audit, based on local Australian experience, has confirmed that UAE is a safe and highly effective treatment for women with symptomatic fibroids and/or adenomyosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Since 2000—associated with the introduction of treatments such as the levonorgestrel-releasing intrauterine system (Mirena™) and second-generation endometrial ablation techniques—the rate of hysterectomy has fallen [ 4 ]. Over the same period nonsurgical treatments for fibroids such as uterine artery embolization and focussed ultrasound also might be expected to reduce further the rate of hysterectomy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000—associated with the introduction of treatments such as the levonorgestrel-releasing intrauterine system (Mirena™) and second-generation endometrial ablation techniques—the rate of hysterectomy has fallen [ 4 ]. Over the same period nonsurgical treatments for fibroids such as uterine artery embolization and focussed ultrasound also might be expected to reduce further the rate of hysterectomy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of leiomyomatous proliferation in our case was significant and prominent. In retrospect, recommending uterine artery embolization (UAE) pretransplant would have been very beneficial for this patient, as studies have shown this procedure carries > 90% success rates in reducing the sizes of, and pain from, fibroids and menorrhagia [16]. Care needs to be taken, however, during the approach for UAE because the main access to the internal iliac artery for embolization is via the contralateral femoral artery and external iliac artery.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional radiologists will also need to take greater clinical ownership for post‐procedural care and this involves having an inpatient bedcard and continuing to post‐operatively manage their patient. These issues form a major hurdle for the provision of these services in many public hospitals …”
Section: The Australian Experiencementioning
confidence: 99%